3, 4, 5-O-tricaffeoylquinic acid with anti-radiation activity suppresses LPS-induced NLRP3 inflammasome activation via autophagy in THP-1 macrophages. (July 2022) - Liu, Jiajun; Chen, Jingyun; Xu, Baixue; Lin, Long; Liu, Shaoqun; Ma, Xiaoying; Liu, Jianwen
Abstract: Damage to normal tissues caused by excessive ionizing radiation (IR) exposure is the major side effect of radiotherapy. Several recent studies have shown that IR-induced damage to tissues leads to a systemic immune response and NLRP3 inflammasome activation in immune cells. 3, 4, 5- O -tricaffeoylquinic acid (tCQA), extracted from the natural plant Azolla imbricata, relieves inflammation and has radioprotective function. Here, we aimed to investigate the inhibitory effect and molecular mechanism of tCQA on IR-induced NLRP3 inflammasome activation. First, the results of ELISA and qPCR assays showed that tCQA has anti-inflammatory effects in THP-1 cell line and healthy human peripheral blood mononuclear cells. Western blotting and ELISA suggested tCQA could inhibit NF-κB/MAPK signaling pathway, NLRP3 expression and the secretion of IL-1β in lipopolysaccharide (LPS)-stimulated THP-1 macrophages. Then, flow cytometry, LDH assay and western blotting demonstrated that tCQA could inhibit LPS- and nigericin-induced Caspase-1 activation and gasdermin D cleavage, thereby suppressing inflammatory cell death. Furthermore, we found that the autophagy inhibitor chloroquine, not the proteasome inhibitor MG132, could counteract the promoting effect of tCQA on NLRP3 degradation and the inhibitory effect on cell death. Western blotting and autophagosome staining results suggested tCQA could significantly enhance LPS-induced autophagic flux in macrophages and ATG5/ATG7 knockdown reverses the inhibitory effect of tCQA on NLRP3 expression and Caspase-1 activation, indicating that tCQA induces NLRP3 degradation via autophagy. Finally, THP-1 macrophages and BALB/c mice were irradiated with 137 Cs γ-rays and tCQA could inhibit IR-induced NLRP3 inflammasome activation both in vitro and in vivo. To conclude, tCQA controls inflammation and NLRP3 inflammasome activation in vitro via NF-κB/MAPK signaling pathway and autophagy, meanwhile inhibits IR-induced NLRP3 inflammasome activation in vivo. Overall, our study provides an experimental and theoretical basis for the application of tCQA as a radioprotectant in clinical radiotherapy. Graphical Abstract: ga1 Highlights: TCQA inhibits inflammatory response though NF-κB/MAPK pathways. TCQA inhibited NLRP3 inflammasome activation in THP-1 macrophages. TCQA affects the autophagic degradation of NLRP3. TCQA alleviates IR-induced NLRP3 inflammasome activation in vitro and in vivo.